Peningkatan Kualitas Pendidikan Anak Luar Sekolah (Homeschooling) Melalui Pelatihan dan Bimbingan Bagi Orang Tua di Bandar Lampung - Muhammad Ferdiansyah; Sugeng Dwiono; Lidia Olga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Children's education, through the homeschooling method, is increasingly in demand in Bandar Lampung. However, many parents need guidance and understanding to run homeschooling effectively. This activity aims to improve the quality of homeschooling education by providing training and guidance to parents. It is hoped that children who participate in homeschooling will receive an education equivalent to formal education standards. The methods used in this activity include practical training and direct guidance to parents who choose homeschooling as their child's education method. Activity participants are provided with knowledge about relevant curricula, effective teaching methods, and appropriate educational resources. Apart from that, they are also taught how to develop their children's social and emotional abilities. The results of this activity showed a significant increase in parents' understanding of homeschooling as an effective educational method. So they are able to design a curriculum according to needs, apply effective teaching methods, and support children's development in various aspects. This community service activity makes a positive contribution in improving the quality of homeschooling education in Bandar Lampung. Parents who take part in this training and guidance program become better able to guide their children's education outside the formal school context.